Analisis Pendekatan Kontekstual dalam Pembelajaran Menulis Cerita Pendek Siswa Kelas VII SMP Negeri Satu Atap Riangpuho - Maria Asumpta Weda Sogen; Vinsensius C. Lemba; Sirilus Karolus Keroponama Keban (Social Science Academic, 2023)
This study aims to provide an overview and explanation of (1) the contextual approach used by the teacher in learning to write short stories, (2) the factors that influence the teacher's success in analyzing contextual approaches, especially learning short stories and (3) the results achieved from applying this approach this contextual. The subjects of this study were Indonesian teachers and Grade VII students of One Roof Public Middle School Riangpuho and the object of the study was short story learning using a contextual approach. Data collection methods used are observation, interviews and documentation. Data obtained through these three methods were analyzed using descriptive qualitative. The results of the study showed that there was an increase in writing short stories using a contextual approach as follows: (1) contextual learning really helps students in the learning process, especially in writing short stories, especially writing experiences; (2) the teacher acts as an informator, motivator, facilitator, evaluator, inspirer, and mediator. Students have a high enthusiasm for learning because it is in accordance with their life experiences, and the school environment supports learning. Meanwhile, the use of language that is easy for students to understand, the deepening method used by the teacher, namely associating the material with students' daily experiences and the intense assistance that the teacher provides when students begin to write stories, are supporting factors in the application of a contextual approach; (3) the results obtained by students from 29 people have a value above the average of 83.66. This shows that learning using a contextual approach can increase the value of short stories to students.